The use of social media networks for healthy nutritional practices by deaf and hearing students - Ziyad K Ellala, Balkees Abuawad; Abdoulaye Kaba
Background: Social media networks such as Facebook, Twitter, WhatsApp, and YouTube are among the most commonly used social networks among people. If used properly, they can contribute to enhancing individual knowledge and scientific values. Aim: The study aimed to investigate the use of social media networks for healthy nutritional practices among deaf and hearing students. Methods: The sample of the study consisted of 103 students (50 deaf and 53 hearing). The researchers used a descriptive approach and adopted a questionnaire for data collection. Results: The findings of the study showed that the use of social media networks for healthy nutritional practices among deaf and hearing students was at a moderate level. However, there were statistically significant gender differences in the average responses of deaf and hearing students in the use of social media networks for healthy nutritional practices. For the status of students (deaf and hearing students), there were statistically significant differences in the average responses to the use of social media networks for healthy nutritional practices. Conclusion: Social media networks play an important role in raising awareness and promoting healthy nutrition practices for both deaf and hearing students.